ПРОСТОРОВО-ВЕКТОРНЕ КЕРУВАННЯ ПАРАЛЕЛЬНИМИ АКТИВНИМИ ФІЛЬТРАМИ - Чопик , В.В.; Михальський , В.М.; Поліщук , С.Й.; Соболєв , В.М.; Шаповал , І.А. (Інститут електродинаміки НАН України, Київ, 2013)
Control features of shunt active filters using space-vector approaches are considered. Simplified analytical expressions for the current compensation using p-q-r instantaneous power theory are received. The space-vector control algorithm of compensator currents regardless of the power converter topology of the active filter is proposed. The boundaries of the correct operation of active filters for any power topologies are determined using the proposed algorithms. The main directions of optimizing quality and quantity of active filters are described. Application of matrix converters in active filters using algorithms that provide maximum possible control range of the input reactive power is proposed. The mathematical simulation of the proposed algorithms which confirms the basic theoretical results of the research is carried out. References 6, figures 8.